رفع القدرة التنافسية للمنشأة من خلال الكشف عن الطاقة الإنتاجية غير المستغلة باستخدام نظام (TDABC) _ دراسة تطبيقية _ - الدبس, محمد هيثم (Latakia University Journal - Economic and Legal Sciences Series, 2016)
عمدت هذه الدراسة إلى تطبيق نظام التكلفة على أساس النشاط الموجه بالوقت(TDABC) في بيئة الصناعات السورية، بهدف التعرف على قدرة هذا النظام في الكشف عن الطاقة الإنتاجية غير المستغلة ضمن موارد المنشأة، وتحديد تكلفة هذه الطاقة، لما لذلك من دور مهم في تخفيض تكاليف الإنتاج ورفع القدرة التنافسية للمنشأة. تم تطبيق نظام (TDABC)ضمن إحدى المنشآت الصناعية في محافظة ريف دمشق، وأدى استخدام نظام (TDABC) إلى الكشف عن وجود طاقة إنتاجية غير مستغلة في أحد أقسام المنشأة محل التطبيق، وتمثل ما نسبته 27% تقريباً من إجمالي تكاليف موارد القسم، بالإضافة إلى تحديد تكلفة هذه الطاقة الإنتاجية غير المستغلة؛ في حين لم يظهر نظام محاسبة التكاليف المطبق في المنشأة أي دلالة على وجود طاقة إنتاجية غير مستغلة في أي قسم من أقسام المنشأة الإنتاجية. خلصت هذه الدراسة إلى أن نظام (TDABC) يستطيع الكشف بطريقة سهلة ومتطورة عن الطاقة الإنتاجية غير المستغلة، ويقوم بتحديد تكلفتها، إضافةً إلى سهولة تطبيق هذا النظام في المنشآت الصناعية. This study aim to apply Time-Driven Activity-Based Costing (TDABC) in Syrian industrial environment to define the ability of (TDABC) in recognition ofidle resources and calculating the cost of it, because of the critical role of this recognition in reducing production cost and inducing entity’s competitive force. (TDABC) has been applied in one of the industrial entities in Damascus Rural. Applying (TDABC) in this entity led to the presence of unused production capacity in one of the entity's sections which representing 27% of the total costs of the resources division, in addition to determine the cost of this unused production capacity, while the adopted accounting cost system in the entity couldn't discover unused production capacity in any section of entity. This study revealed that (TDABC) succeeded in defining idle resources in the chosen entity, and showed the simplicity of applying this method.